Accuracy of Swanepoel Method in Calculation of Polymer Film Thicknesses - Sarunrit Kesornkhup; Adisorn Tuantranont; Tanom Lomas; Chakrit Sriprachuabwong; Kamol Wasapinyokul (Acta Physica Polonica A, 2021)
We studied the accuracy of the Swanepoel method in the calculation of thicknesses of spin-coated poly(methyl methacrylate) films with thicknesses up to 2500 nm. Their thicknesses were calculated by using the Swanepoel method and subsequently compared with the measured actual values. Results showed that both thicknesses followed identical trends where films with higher solution concentrations or slower spin-coating speeds were thicker. The relative difference between the Swanepoel and the actual thicknesses was explained through the thickness of the flat region where the interference of transmitted light occurred. For a film whose flat region was thinner or thicker than other features of the film, its Swanepoel thickness was lower or higher, respectively, than the actual average value. Errors of the Swanepoel thicknesses from the actual values were analysed to find their correlation with the film surface roughness and thickness. When the film roughness and thickness increased fivefold, the error increased threefold and 1.6 times, respectively, indicating that the effect of the film roughness was predominant. Mathematically, this effect was the result of the fact that when roughness increased, the interference pattern shrank, and hence the values deviated. For the effect of thickness, thicker films had higher roughness, and consequently higher errors. Errors of as low as 5% and 0.86% were observed for films with the roughness of less than 15 nm and those with the thickness of 1800 nm, respectively. This showed that the method can be used to calculate the thickness of m-thick polymer films, with a good level of roughness, with satisfying accuracy.
Keywords: Surface Roughness and Optical Measurements; Rheology and Fluid Dynamics Studies; High voltage insulation and dielectric phenomena